Retrospective single-center analysis of surgical treatment of patients with primary mitral insufficiency - О.A. Myshakivskyy; V.H. Аverchuk; А.V. Ratych; I.S. Protsyk; I.P. Chornenkyy; D.V. Аverchuk; T.B. Rudyk; Yu.A. Ivaniv; L.V. Povalyashko; D.S. Tymchuk; V.I. Pavliuk; L.Ya. Solovey; et al. (Кардіохірургія та інтервенційна кардіологія)
The aim – to evaluate the results of the surgical treatment of primary mitral insufficiency (MIS) in single-centre study during three years. Materials and methods. The results of the mitral valve surgery performed from January 2010 to December 2012 in 144 consecutive patients with primary MIS have been analyzed. Registration of all parameters was performed using data of in-patient case reports. Severity of MIS and NYHA functional class (FC) before and after surgery were evaluated. Results. Degenerative channges were a most frequent (54.2 %) cause of MIS. Chordal rupture most a most frequent immediate cause (53.5 %). Mitral valve repair was performed in 51 (35.4 %) patients, replacement – in 93 (64.6 %) patients. The duration of the in-hospital stay in the group of repair treatment was 14 (6–73) days, after replacement – 21.5 (8–63) days (p < 0.05). NYHA FC improved after surgery in 57 (39.7 %) persons, worsened – in 9 (6.3 %), remained stable im more than half of patients. This shows efficiency of pre-surgery drug preparation. Conclusions. The duration of the in-hospital stay depended on type of the surgery and didn’t depend on NYHA FC. It was lower after mitral valve repair. Severity of MR decreased in all patients after mitral valve repair.